Effect of schiff base combination on liver cancer - Doğan, Ayşegül; Başak, Nandini Pal; Telci, Dilek; Dede, Bülent; Kılıç, Ertuğrul; Kılıç, Kübra; Şahin, Fikrettin (Wiley-Blackwell, 2013)
[Abstract Not Available]
38th Congress of the Federation-of-European-Biochemical-Societies (FEBS) -- JUL 06-11, 2013 -- Saint Petersburg, RUSSIA
WOS: 000325919202043
Keywords: Effect of Schiff; Base Combination; Liver Cancer